Radiative Magnetohydrodynamic Flow Over a Vertical Cone Filled With Convective Nanofluid - Prasad, J.L. Rama; Rao, I.V. Venkateswara; Balamurugan, K.S.; Dharmaiah, G. (Communications in Mathematics and Applications, 2022)
This article describes the magnetohydrodynamic radiative nano convective flow over a cone. Brownian motion and thermophoresis effects in nanofluid transport R-K method is used to compute the solutions to the governing non-dimensional partial differential conservation equations and free stream boundary conditions. Numerous thermo-physical parameters were presented, There is a detailed explanation of the simulations as well. Magnetic parameter increases, reduce velocity. According to the findings, there are numerous applications for heat exchanger technology, including geothermal energy storage and cooling, solar energy systems, and materials processing.